Autorzy:Praca zbiorowa
Wydawnictwo:WSiP
Rok wydania:2013
Oblicz 4.6 gwiazdek na podstawie 5 opinii

`a)\ (2^-1+3^-1)^-1=` `(1/2+1/3)^-1=` `(3/6+2/6)^-1=` `(5/6)^-1=6/5=1 1/5` 

 

`b)\ (-0,5)^-2-0,3^-3-1^-5=` ` ` `(-1/2)^-2-(3/10)^-3-1=` 

`\ \ \ =(-2)^2-(10/3)^3-1=` `4-1000/27-1=` `4-37 1/27-1=` `-34 1/27` 

 

`c)\ (4/5)^-1+(-2 2/3)^-2=` `5/4+(-8/3)^(-2)=` `5/4+(-3/8)^2=` 

`\ \ \ =5/4+9/64=`  `1 1/4+9/64=` `1 16/64+9/64=` `1 25/64` 

 

`d)\ (-(1/2)^-2-(1 3/5)^-1*(-8))/(29^0-10^-2)=` `(-2^2-(8/5)^-1*(-8))/(1-(1/10)^2)=` 

`\ \ \ =(-4-5/8*(-8))/(1-1/100)=` `(-4+5)/(99/100)=` `1/(99/100)=100/99=1 1/99` 

   

  ` `  

  ` `